A code comparison of the interaction between Milky Way disc and satellites - Mazzarini, Matteo; Just, Andreas (Proceedings of the International Astronomical Union, 2018)
We present a comparison of previous simulations of the interaction of the Galactic disc with the Milky Way (MW) satellites using superbox-10 with new simulations performed with gadget-2 and ChaNGa. The robust performance of gadget-2 motivates us to employ more recent versions of gadget - to identify the satellite debris in the MW halo, disc and bulge.
Gesehen am 03.09.2019